Analisis Pengawasan, Peralatan, Dan Faktor Resiko Terhadap Kinerja Bongkar Muat Di Pelindo Tanjung Pandan - Kusdibyo Kusdibyo (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research aims to analyze the influence of loading and unloading workers (TKBM), supervision, equipment capacity, risk factors on loading and unloading performance at PT. Indonesian Harbor (Persero) Tanjung Pandan. The analysis used is the Multiple Linear Regression Model. Independent variables include Loading and Unloading Labor, Supervision, Equipment Capacity, Risk Factors. while the dependent variable is Loading and Unloading Performance. The results show that the Risk Factor variable has a correlation with the Equipment Capacity variable with a correlation level of 0.078, where this figure is smaller than 0.90, so multicollinearity does not occur; The Risk Factor variable has a correlation with the TKBM variable with a correlation level of -0.017, where this figure is smaller than 0.90, so multicollinearity does not occur; The Monitoring variable has a correlation with the Risk Factor variable with a correlation level of -0.218, where this figure is smaller than 0.90, so multicollinearity does not occur. Managerial implications of this research include that the number of worker gangs has an influence on loading and unloading performance at PT. Port of Indonesia (Persero) Regional II Tanjung Pandan, so the number of worker gangs needs to be increased further by adding workers, replacing older workers, and providing training to loading and unloading workers to achieve smooth loading and unloading at the port so that loading and unloading performance will increase. TKBM, Supervision, Equipment Capacity and Risk Factors in this research are very important factors in influencing Loading and Unloading Performance at PT. Indonesian Port of Tanjung Pandan.